DIFFERENTIATED INSTRUCTIONAL METHOD: THE INDICES OF SUCCESS AND BOTTLENECKS IN BONNY ISLAND - Aluko; Oluyemisi Christiana; Ayantunji; Mojirade (Adisam Publisher, 2026)
The mainstream system of learning often neglects students with learning needs. Hence, the study investigated the level of knowledge of Differentiated Instructional Methods (DIMs), teacher proficiency, successes, barriers to implementation, and the effect of DIMs on individual learning outcomes in Bonny Island. A structured questionnaire was administered and classroom observation was conducted for data collection. The sample population consisted of 50 teachers. Results showed that there was a high level of DIM awareness. However, the success of DIMs varied among schools. 15% of the teachers adopted DIMs. This significantly impacted the learning outcome. Inadequate training, insufficient learning resources, space, lesson preparation time, and lack of support staff were barriers to DIM implementation. A high-class population (30-44) disrupted learning. DIM implementation is imperative to cater to the needs of all children. Pre- and in-service training on DIMs and proper funding and monitoring of schools should be adopted to improve DIM application.